Impact of Bilingualism on Infants' Ability to Learn From Talking and Nontalking Faces. (24th November 2017) - Fort, Mathilde; Ayneto‐Gimeno, Alba; Escrichs, Anira; Sebastian‐Galles, Nuria
Abstract: To probably overcome the challenge of learning two languages at the same time, infants raised in a bilingual environment pay more attention to the mouth of talking faces than same‐age monolinguals. Here we examined the consequences of such preference for monolingual and bilingual infants' ability to perceive nonspeech information coming from the eyes or the mouth region of talking faces. Using a learning procedure, we recorded 15‐month‐olds' and 18‐month‐olds' gaze while watching, at each trial, a speaker producing a sentence systematically followed by a nonspeech movement (eyebrow raise vs. lip protrusion). Differences were obtained for infants in the eyebrow‐raise condition. While 15‐month‐old monolinguals and 18‐month‐old bilinguals learned to anticipate the eyebrow‐raise movement before its appearance, 15‐month‐old bilinguals did not (i.e., they continued to look at the mouth region). Thus, bilingualism appears to impact not only how infants explore talking faces but also how they learn from them.